2008
DOI: 10.1007/s00011-008-8053-2
|View full text |Cite
|
Sign up to set email alerts
|

Platonin inhibits LPS-induced NF-κB by preventing activation of Akt and IKKβ in human PBMC

Abstract: These results suggest the anti-inflammatory activity of platonin is a result of reduced NF-kappaB activity due to inhibition of Akt and IKKbeta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
(26 reference statements)
3
14
0
Order By: Relevance
“…The effect of violaxanthin on NO and PGE 2 production was consistent with the carotenoids, where β-carotene, lutein, and fucoxanthin were shown to suppress NO production. [36][37][38] Violaxanthin concentrations of 30 and 60 µM significantly inhibited LPSinduced NO production by RAW 264.7 cells. At 60 µM, violaxanthin significantly inhibited NO production by as much as L-NMMA.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The effect of violaxanthin on NO and PGE 2 production was consistent with the carotenoids, where β-carotene, lutein, and fucoxanthin were shown to suppress NO production. [36][37][38] Violaxanthin concentrations of 30 and 60 µM significantly inhibited LPSinduced NO production by RAW 264.7 cells. At 60 µM, violaxanthin significantly inhibited NO production by as much as L-NMMA.…”
Section: Discussionmentioning
confidence: 93%
“…36,40,41) These observations indicate that reactive oxygen species are related to inflammatory gene expression though the NF-κB signaling pathway. Recently, violaxanthin was reported to have strong antioxidant properties in oxidative stress and function as a chain breaking antioxidant in lipid peroxidation.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, we explored the nuclear levels of NF-kB in EOL-1 and EOL-1R cells (Figure 4c), because AKT is known to stimulate NF-kB activity. 22,23 Notably, EOL-1R cells expressed a greater amount of NF-kB in their nucleus in association with the upregulation of p-IKK and downregulation of IkBa in their cytoplasm, suggesting activated NF-kB signaling in these cells (Figure 4c). Imatinib induces epigenetic silencing of the PTEN gene C Nishioka et al…”
Section: Effect Of Imatinib On Antiapoptotic Proteinsmentioning
confidence: 97%
“…The liberated NF-kB translocates to the nucleus, where it binds with the promoter region of various target genes. 22,23 Previous studies showed that the expression of PTEN was downregulated by the homozygous deletion of the PTEN gene in various types of cancers and the loss of the PTEN protein was associated with poor prognosis. [24][25][26][27] In addition, epigenetic silencing of the PTEN gene was found in advanced human prostate cancer, hematologic malignancies, endometrial carcinoma as well as malignant melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the elevated levels of interleukin (IL)-1b, IL-6, and tumor necrosis factor (TNF)-a induced by systemic administration of lipopolysaccharide (LPS) in rabbits are attenuated by pretreatment with platonin [5]. In peripheral blood mononuclear cells, platonin suppresses the production of proinflammatory cytokines, nitric oxide (NO) production, and inducible NO synthase (iNOS) expression induced by LPS [12]. Targeting proinflammatory cytokines with anti-TNFa and anti-IL-1b antibodies has a beneficial effect on engraftment of islet grafts [13].…”
Section: Introductionmentioning
confidence: 99%